Anti-angiogenic and anti-hepatocellular carcinoma properties of zerumbone extracted from Zingiber Zerumbet (l.) Smith - Abdul Samad, Nozlena (2015)
Zerumbone (ZER) extracted from Zingiber zerumbet is known to have anti-cancer properties; however, its mechanism in curbing liver cancer growth and spread is still not clear. Thus the objective of this study is determine the in vitro anti-cancer effect of ZER towards HepG2 cell line and the in vivo effect on induced rat hepatocellular carcinoma (HCC). The anti-cancer mechanisms investigated were apoptosis, antiproliferation and anti-angiogensis. Zerumbone was shown to be toxic towards HepG2 cells with IC50 of 6.20±0.70 µg/mL and less toxic towards normal liver cells (WRL68) with IC50 of 61.00±0.40µg/mL. The study showed that ZER caused cell cycle arrest at the G2/M phase and apoptosis, demonstrated by chromatin condensation, cell shrinkage and formation of apoptotic bodies in the HepG2 cells in a time-dependent manner. Zerumbone also stimulated caspase-3 and -9 activities in the HepG2 cells, suggesting that the induction of apoptosis was via the mitochondrial pathway. The study employed the diethylnitrosamine-induced rat HCC model and the rat aortic ring to determine the effect of ZER treatment. The study showed that ZER significantly (p<0.05) inhibited microvessel outgrowth in the aortic ring model. Zerumbone at 12.5 µg/mL caused the most significant (p<0.05) 98±1.28% blood vessels inhibition compared with the control and inhibited endothelial tube formation at 96.00±0.72%. This study showed that ZER treatment decreases expression of VEGF, MMP-9 and Ki- 67 in the rat HCC tissue as well as and inhibits neovascularization in the chick embryo. The treatment had also induced apoptosis in HCC. The ZER-treated liver tissues with HCC showed normal hepatocyte orientation, unlike the untreated livers, which showed pleomorphic hepatocytes and anaplastic appearance typical of HCC. It can be concluded from the study that the anti-cancer effect of ZER on the HepG2 cell line and HCC is multifaceted involving induction of cell cycle arrest, apoptosis, and suppression of VEGFR, VEGF, MMP-9 and Ki-67 proteins, leading to inhibition of angiogenesis. Since ZER was less toxic to the normal liver cells, this compound is a potentially effective anti-HCC agent, without significant side-effects and can be developed as a therapeutic regime either alone or in combination with other chemotherapeutic agents.